Pregnancy in endurance athletes - Penttinen, J.; Erkkola, R. (Scandinavian Journal of Medicine & Science in Sports, 1997)
The purpose of the present study was to examine pregnancy and delivery among Finnish endurance athletes at the national top level. A questionnaire concerning first pregnancy was sent to 30 Finnish endurance athletes who had been at national top level in cross-country skiing, running, speed-skating or orienteering. Data on labour were collected retrospectively through a questionnaire and from the diaries in the hospital concerned. The next primipara in the diaries formed a member of the control group. Twenty-three athletes (77%) had regular menstrual cycles, seven (23%) had irregularities, and four of them had received hormonal treatment for this. Seven athletes (23%) had experienced spontaneous abortion during the first trimester in previous pregnancy. Sixteen (53%) did not notice any change in their exercise performance, three (10%) subjectively felt themselves to be in a better physical condition, and seven (23%) felt themselves to be in a worse condition than before the pregnancy. Four did not respond on the question. After delivery, 18 athletes continued to compete, the median interval being 8.2 months (range 2-24 months). Two of them (11%) achieved a better condition than before the pregnancy, 11 (61%) reached the same level and five (28%) did not achieve the same performance level. There were no significant differences in labour parameters between the athletes and controls. Endurance training had no harmful side-effects on the pregnancies or deliveries of the athletes. The effect of pregnancy on exercise performance is individual.